Real-world outcomes of mepolizumab treatment in severe eosinophilic asthma patients - retrospective cohort study in Slovakia - Jesenak, Milos; Vanecek, Vaclav; Ondrusova, Martina; Urdova, Veronika; Dostalova, Katarina; Hochmuth, Ludek (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2023)
AIMS: Mepolizumab, a fully-humanized recombinant IgG1 kappa monoclonal antibody directed against IL-5, has shown improved asthma control and lung function in randomised controlled trials. The aim of this study was to evaluate real-world clinical experience in patients with severe eosinophilic asthma treated with mepolizumab in Slovakia. METHODS: A retrospective, non-interventional study based on medical records of all adult asthma patients initiating mepolizumab between November 1, 2017 and January 31, 2019, completing 12 months of treatment. At baseline, general and clinical profile data were recorded 12 months prior to treatment. Primary and secondary endpoints described the results of mepolizumab use at 2, 6, and 12 months after the initiation and compared to baseline. Statistical testing of individual change (in each patient) in selected parameters was performed. RESULTS: The cohort included 17 patients with particularly severe asthma at baseline, with frequent severe exacerbations (SE, median 5 [IQR 4-6]/patient/year), high blood eosinophil counts (median 0.6x109/L), frequent oral corticosteroid (OCS) dependence (82.35%), median dose 15 (IQR 7.5-20) mg/day, impaired lung function, and a spectrum of comorbidities. In a one-year follow-up, the data showed reductions in median SE (0 [IQR 0-1] patient/year, eosinophilia (median 0.175x109/L) and OCS maintenance dose (median 6.25 [IQR 2.5-20] mg/day), all statistically significant after 12 months on mepolizumab. Improved and stabilised lung functions throughout the cohort and a reduced incidence of nasal polyposis were observed. CONCLUSIONS: The results provide clinical evidence of mepolizumab efficacy in a real sample of patients with severe asthma when administered in routine care settings in Slovakia.
Keywords: dospělí; retrospektivní studie; Humans; bronchiální astma; Asthma; mepolizumab; Eosinophilia; Slovakia; real world evidence; severe eosinophilic asthma; Slovenská republika; Anti-Asthmatic Agents; Adult; eozinofilie; antiastmatika; exacerbations; lidé; Adrenal Cortex Hormones; hormony kůry nadledvin; Retrospective Studies